Manajemen Komunikasi Pelestarian Budaya Seni Tari Pada Sanggar â€œPotre Konengâ€ Kabupaten Sumenep - Fauzuna , Hafidlatul (Jurnal Komunikasi Nusantara, 2021)
Today, the art of dance is being destroyed so that it requires preservation effort, in order to maintain its sustainability in the midst of society. This is what the Potre Koneng dance studio in Sumenep Regency is doing, namely by managing good communication so that efforts to preserve the art of dance take place well. This study uses a qualitative descriptive approach with data collection techniques using interviews, observation and documentation. The result showed that the communication management carried out in the Potre Koneng dance studio used an adult communication model which was analogous to the "Russian Matouschka dolls", which consisted of self doll, interpersonal doll, people-in-system doll, and competence doll components. Self doll was done in the form of contact, involvement and intimacy. Interpersonal doll was done in the form of empathy, supportive attitude, positive attitude, and an equality. The people-in-system doll was depicted by messing with the humanistic design between the Potre Koneng dance studio and the community. Meanwhile, competence doll covers all layers or sizes of the previous doll. The obstacles in communication management at the Pore Koneng dance studio are the noise during practice and the existence of suspicious prejudices. Keywords: communication management; dance art; cultural preservation